An exploration of physical activity and wellbeing in university employees. (May 2016) - Cooper, Kay; Barton, Gillian C
Aims: The aim was to explore levels of physical activity (PA) and mental wellbeing in university employees, as well as barriers to and incentives for workplace PA. Methods: An electronic survey was distributed to all staff at one UK university. The survey consisted of a PA stages of change questionnaire, an international PA questionnaire (short-form), the Warwick-Edinburgh Mental Well-being Scale (WEMWBS), questions on perceived barriers to and incentives for workplace PA, questions on methods of enhancing employee wellbeing and demographics. A self-selected sample participated in two focus groups to explore key themes arising from the survey. Descriptive statistics were reported for survey data; associations between PA and wellbeing were tested for using Kruskal–Wallis with post hoc Mann–Whitney. Descriptive, thematic analysis was performed on focus group transcripts. Results: A total of 502 surveys were completed (34% response rate); 13 staff participated in focus groups. In all, 42% of the sample reported PA below the recommended guideline amount. Females were less active than males ( p < 0.005). The mean WEMWBS was 49.2 (95% confidence interval (CI): 48.3–49.9). Low PA levels were related to lower WEMWBS scores, with statistically significant differences in WEMWBS demonstrated between low and moderate PA ( p = 0.05) and low and high PA ( p = 0.001). Lack of time and perceived expense of facilities were common barriers to workplace PA. The main focus group finding was the impact of university culture on workplace PA and wellbeing. Conclusion: University staff demonstrate PA levels and a relationship between PA and wellbeing similar to the general population. Carefully designed strategies aimed at enhancing PA and wellbeing in university staff are required. The specific cultural and other barriers to workplace PA that exist in this setting should be considered. These results are being used to inform PA and wellbeing interventions whose effectiveness will be evaluated in future research.